2005
DOI: 10.1007/s00125-004-1642-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a reference four-component model to define the effects of insulin treatment on body composition in type 2 diabetes: the ?Darwin study?

Abstract: Aims: To define the effects of insulin treatment on body composition and fat distribution, and investigate the potential role of body weight (BWt) gain predictors in patients with poorly controlled type 2 diabetes. , with the FFM increase due solely to total body water [TBW; +2.4 (1.5) l], as there were no detectable changes in total body protein or bone mineral, thereby increasing FFM hydration by 1.3%. More body fat was deposited centrally in patients receiving insulin alone than those receiving insulin with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 35 publications
(57 reference statements)
0
30
1
Order By: Relevance
“…Higher MS in type 1 diabetic patients versus T2D has been reported by Cetinus et al, as compared to age-matched control subjects [21]. The correlation between the decrease in HbA1c and BW gain, and with insulin doses have been reported by other authors [18, 20]. …”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Higher MS in type 1 diabetic patients versus T2D has been reported by Cetinus et al, as compared to age-matched control subjects [21]. The correlation between the decrease in HbA1c and BW gain, and with insulin doses have been reported by other authors [18, 20]. …”
Section: Discussionmentioning
confidence: 62%
“…Overall our results are in agreement with previous studies. In T2D, previous studies reported that BW gain (+1.6 ± 4.9 to +5.2 ± 2.7 kg at six months) was mainly composed of fat [1520]. We confirm the predominance of FM gain in insulin-treated T2D as it represented the entire BW gain; we demonstrated for the first time the absence improvement in MS after insulin therapy in type2 diabetic patients that confirm the absence of improvement in FFM during weight gain in insulin treated T2D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, insulin therapy is associated with weight gain [11,12], predominantly fat mass [13], which increases insulin resistance and necessitates the use of higher doses of insulin at the expense of further weight gain. The exact role of insulin in human skeletal muscle metabolism, however, continues to raise debate.…”
Section: Introductionmentioning
confidence: 99%
“…Waist and hip circumferences were measured according to a standardized protocol (15). Body weight and fat mass were assessed using the Tanita bioimpedance balance (Yiewsley, UK) (26).…”
Section: Oral Glucose Tolerance Testmentioning
confidence: 99%